Research Note: Effect of CPPU (N-(2-Chloro-4-Pyridinyl)-N’- Phenylurea) and a Seaweed Extract on Flame Seedless, Redglobe and Crimson Seedless Grape Quality - Strydom, J. (South African Journal of Enology and Viticulture, 2013)
The application of GA3 (gibberellic acid), in combination with CPPU (N-(2-chloro-4-pyridinyl)-N’- phenylurea), may result in larger berries, but also decreases total soluble solids (TSS), increases total titratable acidity (TTA) and reduces grape skin colour. The purpose of this study was to determine a CPPU dosage that would improve berry size, without negative effects on other quality attributes of Flame Seedless, Redglobe and Crimson Seedless. The trials, which were conducted in the 2008/2009 season, comprised five treatments: control (standard GA3 application), seaweed extract plus GA3, and three dosages of CPPU in combination with GA3. CPPU dosages were 1, 2 and 3 ppm for Flame Seedless; 3, 4 and 5 ppm for Redglobe; and 2, 3 and 4 ppm for Crimson Seedless. The seaweed product used on Flame Seedless and Redglobe was derived from Ascophyllum nodosum, while a derivative of Ecklonia maxima was used on Crimson Seedless. Berry diameter, TSS, TTA, anthocyanin concentration, grape colour as well as cold storage defects were determined. CPPU dosages of 2, 5 and 3 ppm significantly increased berry diameter in Flame Seedless, Redglobe and Crimson Seedless respectively. Five ppm CPPU increased Redglobe TSS. Three ppm CPPU increased TTA and decreased anthocyanin concentration in Crimson Seedless. The seaweed extract treatment resulted in firmer Flame Seedless berries with a higher anthocyanin concentration than the control. Seaweed extract also improved the firmness of Crimson Seedless compared to the control. Four ppm CPPU increased the percentage of Crimson Seedless total cold storage defects compared to the control.